Encapsulation of clove essential oil in hydroxypropyl beta‐cyclodextrin for characterization, controlled release, and antioxidant activity. Issue 5 (1st February 2017) - Cetin Babaoglu, Humeyra; Bayrak, Ali; Ozdemir, Necla; Ozgun, Nuriye
Abstract: The aim of this study was to investigate the physicochemical characteristics, release behavior, and antioxidant activity of clove essential oil‐hydroxypropyl beta‐cyclodextrin (CEO‐HPβCD) inclusion complexes. Clove essential oil was encapsulated by the kneading method with hydroxypropyl beta‐cyclodextrin in a 1:1 molecular ratio. The entrapment efficiency of the encapsulated particles was 97.04% ± 1.57. The average particle size was 165.87 ± 1.65 nm and polydispersity index was .25 ± .03. In vitro release profile of CEO‐HPβCD inclusion complexes indicated slow and sustained release. DPPH scavenging activity of free clove essential oil and encapsulated particles was 25.20% ± 1.02 and 28.70% ± .77, respectively. Total phenolic content of free clove essential oil was 18.59 ± 1.60 mg GAE/100 mg oil while total phenolic content of particles was 22.57 ± 1.48 mg GAE/100 mg oil. The results of the study revealed that using hydroxypropyl beta‐cyclodextrin to encapsulate clove essential oil can be beneficial for the food and pharmaceutical industries. Practical applications: Clove essential oil has many biological activities due to its major compound eugenol. Choosing the appropriate method is a significant step for keeping active constituents. Encapsulation that is a beneficial process to control of the bioactive components can prevent degradation and loss of active compounds and prolong the shelf life of entrapped materials. This study can lead to use kneading method which is a low cost and easy encapsulation technique, for conservation of volatile active components, so these compounds can be used more intensely in the form of powder.